Strength of Non-traditional Granular Materials Assessed from Drained Multistage Triaxial Tests. (2016) - Reis Ferreira, S.M.; Correia, A. Gomes; Roque, A.J.
Abstract: When granular materials are applied in geotechnical works, like embankments and road pavement layers, one of the most relevant engineering properties in stability analysis is ultimate shear strength. In geotechnical engineering, the triaxial test is one of the most reliable methods available for determining ultimate shear strength. In this test, a soil specimen, compacted in laboratory or collected from exploratory soil borings, is generally used. In order to determine the strength parameters, at least 3 identical specimens are required in this test. Having 3 identical specimens, a single stage triaxial test procedure is used. If not, multistage triaxial test procedure is used to eliminate the effects of soil variability in the results. In this case, several confining pressures are applied to the same specimen. Although multistage triaxial tests have been used for soils for a long time, there is still a lack of test results for unbound granular non-traditional materials. This paper presents triaxial test results obtained from a Portuguese unbound granular non-traditional material (named as Inert Steel Aggregate for Construction - ISAC). The triaxial tests were carried out using multistage and single stage techniques. As the results are quite well comparable, it is concluded that it is possible to determine shear strength parameters with just one specimen. Consequently, the research conducted has validated the use of multistage triaxial tests as a reliable and cost-effective alternative to the conventional single stage triaxial test in the mechanical characterization of unbound granular materials.